-
f(x)=x^3+bx^2+cx+d
Because p(0,2), f(0)=d=2
f'(x)=3x^2+2bx+c
f(-1)=(-1)^3+b(-1)^2+c(-1)+d=-1+b-c+d=-1
i.e. b-c+d=0, b-c=-2
f'(-1)=3(-1) 2+2b(-1)+c=3-2b+c=0, i.e., 2b-c=3
The simultaneous solution is b=5, c=7
The analytical formula for f(x) is f(x)=x 3+5x 2+7x+2f'(x)=3x2+10x+7=(3x+7)(x+1)let f'(x)=0 The solution of x=-1 or x=-7 3 is easy to obtain x=-7 3 is the maximum point, and x=-1 is the minimum point.
So f(x) monotonically increases in the interval (-infinity, -7 3) and (1, + infinity) monotonically decreases in the interval (-7 3, -1).
Look at the time in order!! Thank you for your satisfaction!!
-
f(x)=x 3+bx 2+cx+d over p(, then:
f(0)=d=2
f(-1)=-1+b-c+2=-1
c=b+2f'(x)=3x 2+2bx+c is given by the known available equation f'(x)=3x 2+2bx+b+2=0 is -1, x+1)(3x+b+2)=0 [decomposition factor].
3+b+2=2b [the primary term is equal to the original equation].
b=5, c=b+2=7
Another: -b+2) 3=-7 3
So y=f(x)=x 3+5x 2+7x+2 from two zeros -7 3,-1 and the opening direction, we can know:
Minus interval (-7, 3, -1).
increase interval (- 7 3), 1,+
-
Solution: Substitute the point p(0,2) into f(x)=x 3+bx 2+cx+d, and get d=2
f(x) is the extreme value of the point x=-1, and f is obtained'(-1)=3x 2+2bx+c=0, i.e. 3-2b+c=0 (1).
f(x) points the extreme value -1 at the point x=-1, and gives f(x)=-1, i.e., -1+b-c+2=-1 (2).
1), (2) synthesis, get b = 5, c = 7
So y=f(x)=x 3+5x 2+7x+2 let f'(x)=3x 2+10x+7=0, x=-1 or x=-7 3 is easy to know x=-7 3 is the maximum point, and x=-1 is the minimum point.
So the monotonically increasing interval of f(x) is (-infinity, -7 3) and (-1, +infinity) monotonically decreasing interval is (-7 3, -1).
-
1. Let the real number solution be m,n
Then: 2m+1=n
1=3-n2m+an=9
n-4m-b=-8 (the i of the second equation is outside) is solved: m=1 2, n=2, a=4, b=8
2. Your question is |z|-z=2i (2+i)?
Let Z=A+Bi
Root(a2+b 2)-a-bi=(2+4i) 5So, root capacity(a2+b 2)-a=2 5
b = 4 5 solution: a = 3 5, b = -4 5
z=3/5-4/5i
-
<1>2x+1=y
1=3-y gives x=1 2, y=2
2x+ay=9 is equivalent to 1+2a=9
y-4x-b=-8 is equivalent to -b=-8
The solution yields a=4 and b=8
2> the topic is not clear enough, isn't "z-z" equal to 0, is it a conjugate plural?
-
There is a real number solution, x, y are real numbers, the real part and the imaginary part in the formula correspond equally, the first formula has 2x+1=y,,1=3-y;;; The second formula has 2x+ay+y-4x=9,b=8;;; Understandable.
-
Solution: a, b are the two inner angles of an acute triangle.
a+b>π/2
a>π/2-b>0, b>π/2-a>0
y=tanx is an increment function on (0, 2).
So tana>tan(2-b), tanb>tan(2-a).
i.e. tana>cotb, tanb>cota, so cotb-tana<0, tanb-cota>0, so z=(cotb-tana)+i(tanb-cota) corresponding to the point (cotb-tana, tanb-cota) is in the second quadrant.
-
The value of the square root of the sum of the squares of the real and imaginary parts of a complex number is called the modulo of the complex number and is denoted as z z = a+i
z∣=√(a^2+1^2)
So the range is (1, 5)c
-
One. Let z=a+bi, by |z-1|=1 to get |a-1+bi |=1, i.e. the square of (a-1) + the square of b = 1....1)
1 z=1 (a+bi)=(a-bi) (a-bi)(a+bi)=(a-bi) (square of a + square of b). From z+1 z as a real number, the imaginary part of z+1 z, i.e., b-b (the square of a + the square of b), must be zero. Simplification, the square of a + the square of b = 1....
2) Simultaneous (1) (2) two formulas, a = 1 2, b = root number 3 2 or b = - root number 3 2
-
Let Z=A+Bi, with Z+1 Z as a real number, and substituting Z into the solution to obtain a 2+b 2=1 from the latter condition (A-1) 2+b 2=1, let's calculate slowly!
-
That is, when 2m2-3m-2 (m2-3m+2).
Derive m 0 or, m 2
In this case, the complex number is -2+2i or 0
-
b, the square of a pure imaginary number is the square of the real number multiplied by the square of i, i 2=-1, so it is a negative real number.
The quantity produced: 1 2 + 1 3 + 1 6
The number of defects: 1 2* + 1 6*, the probability of defects: the number of defects divided by the quantity produced (you can calculate it yourself). >>>More
Mathematics is memorized on the basis of understanding, and prime numbers (also called prime numbers) are divisors with only 1 and itself, so what is a divisor? If the integer a is divisible by the integer b, a is called a multiple of b, and b is called the divisor of a. It's good that you know the Vedic theorem, but some people don't know that there is such a theorem. >>>More
First of all, you have to adjust your mentality, don't be afraid of math, I'm a sophomore in high school, I'm your age, I'm a math master. In fact, I am not a strong player, and my math learning is not top-notch, but I pay attention to my own weaknesses, practice more of my weak question types, and summarize methods. In fact, you should not take the test attitude to learn mathematics, which will make you feel pressured to enjoy the infinite fun that the mystery of mathematics brings you. >>>More
This can be solved using inequalities.
For the real numbers a, b, we always have (a-b) 2>=0, so we have a2+b 2>=2ab >>>More
By the question, there is |f(-1)|= |-a+b|<=1 ; f(1)|= |a+b| <=1 >>>More